PEMANFAATAN LIMBAH DAUN NANAS (Ananas comosus) SEBAGAI BAHAN BAKU PEMBUATAN PLASTIK BIODEGRADABLE - Maria Natalia; Wirananditami Hazrifawati; Doni Rahmat Wicakso (Universitas Lambung Mangkurat, 2019)
Biodegradable plastic (bioplastics) is a polymer that can be degraded and made from renewable sources, including cellulose obtained from pineapple leaves. The purpose of this study is to determine the mechanical properties of bioplastics from cellulose, determine the optimum conditions based on the concentration of chitosan variations on cellulose solution and the addition of glycerol plasticizers to the mechanical properties of biodegradable plastic produced. This study begins with the manufacture of cellulose from pineapple leaves through a process of delignification and bleaching and then making biodegradable plastic 1% cellulose raw material with a variation of chitosan with a variation of 1%; 2%; 3% and the addition of plasticizer glycerol 1%, 2% and 3% (v/v). The results obtained will be observed by tensile tests, SEM tests, swelling tests, and biodegradation. The results obtained in the morphological test with the SEM test showed that cellulose was not evenly distributed. The tensile strength test for the addition of chitosan showed that the concentration of 3% had the highest tensile strength value of 11.8 MPa while the tensile strength of the addition of glycerol showed that the concentration of 3% had the highest tensile strength value of 3.6 MPa. The swelling test shows that glycerol concentration influences biodegradable plastic water resistance and glycerol 3% has the highest percentage of water resistance, 16.6%. In the biodegradable plastic degradation test with 3% glycerol experiencing the fastest degradation, this shows that glycerol has an effect on biodegradable plastic degradation